High fertility in a Peruvian native community Ucayali River - Hern, Warren (2015)
This is an initial study of fertility and cultural changes in a Shipibo people in the Peruvian Amazon. This study was initiated in 1964, to the present, and includes aspects: social, environmental, economic, cultural and health. The population growth in this ethnic group. reaches 5% annually, which is much higher than that found by other researchers, for other groups. Analyzes the factors that contributed to the growth and establishes, among other things, play starts at an early age and continues until it reaches the final stage of reproductive age. It notes that marriage is universal and that its high reproductive capacity, is reflected in its short spacing childbirth and another. It concludes that it is important to educate this group on family planning, in order to reduce maternal and infant mortality, the high birth rate.